PERFORMANCE OF MIZO LOCAL PIGS (ZOVAWK) UNDER TRADITIONAL HOUSING SYSTEM (Indian Journal of Animal Production and Management, 2015)
Ten Zovawk (Mizo local pig) female and two male pigs of 1st parity (4-5 months of age) were selected randomly from a sizable population maintained at Instructional Pig Farm of College of Veterinary Sciences & A.H., Aizwal, Central Agricultural University, Mizoram to study the performance under traditional housing system. The body weight changes of piglets up to 12 week of age showed a linear increase in growth. The conception rate in sows was 100%. Litter size at birth and weaning were 7.3± 0.67 and 6.1±0.71, respectively. The overall mortality was 14.29%. Out of that, 25% piglets died within first week after birth. There were no reports of mortality in piglets between 8-12 weeks of age and adult stages. The majority of pigs died due to respiratory distress associated with pyrexia. The profit/piglet was found to be Rs.611.76 which was remunerating for the rearing system in which farm labour and construction costs of sty were significantly low.
Keywords: Zovawk; Traditional Housing; Performance